The role of international criminal law in responding to the crime–terror nexus - Wilt, Harman van der (European journal of criminology, 2019)
This article seeks to map the possible bottlenecks for international legal cooperation in the context of terrorism and/or organized crime. The assumption is that – because of the crime–terror nexus – any obstacle encountered in that area with respect to the suppression of one form of criminality will backfire on the other form as well. After addressing the indefinite concept of terrorism, and its connection with organized crime, we will look at extraterritorial jurisdiction and international cooperation in criminal matters. In the final section, we will offer a number of concluding observations.